Controverses About Tasawuf In Historical Track Of Development - May, Asmal; Jamarudin, Ade; Mujafer, Ahmed (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2023)
The group that criticized it viewed Sufism as a school and movement that was added to Islam after the period of the Prophet Muhammad. according to them, Sufism is not native to Islam, was never taught and practiced by the Prophet. in their eyes, Sufism is a cult, or at the very least, detrimental to Muslims. Among the Sufis themselves, there are some who criticize others, because the former considers that the latter adheres to false Sufism. The purpose of this research is to straighten out the understanding of Sufism by expressing various rational and proportional arguments and arguments. Perhaps in this way it is hoped that this writing can provide input for a correct understanding of the teachings of Sufism. The method used is a research method with a theological approach. results of this study Historical evidence shows that in general Sufis do not shun worldly life. They make a great contribution in the development of various areas of life. In the field of education, for example, Sufis such as Khface Nizam al-Muluk, the vizier of the Seljuq dynasty, participated directly in building universities and various other educational institutions. Contact with society is the test of progress made towards perfection, for it is only by living with society that the Sufi can demonstrate his freedom from lust and that he has abandoned his ego.